Purification of V2O5 and its application in all-vanadium redox flow batteries. (19th June 2019) - Cui, Xumei; Zhang, Guigang; Chen, Xiaoe; Hou, Bingxue; Zhang, Xuefeng; Lan, Dejun
Abstract: V2 O5 was prepared using chemical impurity removal agents (CaCl2, MgCl2, and Al2 (SO4 )3 ) in impurity removal methods and hydrolytic precipitation of vanadium with industrial grade ammonium vanadate as raw material, and then, VOSO4 electrolyte was prepared with the V2 O5 . The results show that the purity of V2 O5 prepared by hydrolytic precipitation of vanadium is higher than that of the V2 O5 prepared by chemical impurity removal agents (CaCl2, MgCl2, and Al2 (SO4 )3 ) via impurity removal methods, and new impurities (such as Ca, Mg, or Al) are introduced with the latter methods. The electrochemical performance of the VOSO4 electrolyte was evaluated through cyclic voltammetry and AC impedance tests. The experimental results show that the VOSO4 electrolyte created with V2 O5 prepared via hydrolytic precipitation of vanadium have the best electrochemical performance. The VOSO4 electrolytes prepared with V2 O5, created using a chemical impurity removal agent (MgCl2 or Al2 (SO4 )3 ) via impurity removal methods also have better electrochemical activities because of the higher purity of V2 O5, although new impurities, such as Mg and Al, are introduced. The introduction of Ca impurity via the use of the chemical impurity removal agent CaCl2 is not beneficial for the electrochemical performance of the VOSO4 electrolyte, although a higher purity of V2 O5 was achieved. Moreover, the all-vanadium redox flow battery with the electrolyte using V2 O5 prepared via hydrolytic precipitation of vanadium exhibites the best cycling stability and charging and discharging performance with the capacity increasing by approximately 9% compared with that of the unpurified electrolyte.